Functional Characterization of Calcineurin-Responsive Transcription Factors Fg01341 and Fg01350 in Fusarium graminearum - Zhang, Xiangxiang; Cao, Shulin; Li, Wei; Sun, Haiyan; Deng, Yuanyu; Zhang, Aixiang; Chen, Huaigu (Frontiers in Microbiology, 2020)
Ca2+/calmodulin-dependent phosphatase calcineurin is one of the important regulators of intracellular calcium homeostasis and has been investigated extensively in Saccharomyces cerevisiae. However, only a few reports have explored the function of the Crz1 homologue in filamentous fungi, especially in Fusarium graminearum. In this study, we identified Fg01341 as a potential ortholog of yeast Crz1. Fg01341 could interact with calcineurin and initiate nuclear transport in a calcineurin-dependent manner. The ΔFg01341 mutant exhibited normal hyphal growth on basic medium and conidia formation, but sexual reproduction was partially blocked. Pathogenicity assays showed that the virulence of the ΔFg01341 mutant in flowering wheat heads and corn silks dramatically decreased and was thus consistent with the reduction in deoxynivalenol production. Unexpectedly, the sensitivity to osmotic stress of the deletion mutant and that of the wild-type strain did not present any differences. The deletion mutant showed higher sensitivity to tebuconazole than the wild-type strain. Results also showed that the transcription factor Fg01350 might be the calcineurin target and was independent of Crz1. Furthermore, ΔFg01350 showed defects in hyphal growth, sexual production, virulence, and deoxynivalenol production. Collectively, the results indicate that these two proteins functionally redundant and that the calcineurin–Crz1-independent pathway is particularly important in F. graminearum.